Evaluation of Elite Jamun (Syzygium cumini) Germplasm Collections for Fruit Yield and Quality under High Density Planting System in the Northern Telangana Agro-climatic Zone - Murali, V.; Sai Prasanna, G.; Ali, Syed Irfan (International Journal of Bio-resource and Stress Management, 2025)
In the present study, ten elite Jamun genotypes representing different agro climatic zones of India, were evaluated during 2023 fruiting season (February to July) under high density planting (4 m×4 m) established in 2016 at Horticultural Research Station, Adilabad, located in the Northern Telangana Agro climatic Zone. The objectives of the study were to evaluate the elite Jamun genotypes performance in terms of phenological and pomological attributes in the moderately saline clay loam soils. Among the elite genotypes, SRDJC-15 and SRDJC-04, with short stature, and sparse crowns were found to be suitable for high-density planting. Early flowering was observed in SRDJC-15 and ADBJC-01, while SRDJC-04, SRDJC-16, and RNRJC-01 flowered mid-season, and AJG-85 and RNRJC-03 were late bloomers. Significant genetic variability was recorded for fruit yield and quality attributes studied. The germplasm SRDJC-03 had produced the significantly highest fruit yield (22.83 kg tree-1) and was 84.0% higher than Konkan Bahadoli. Whereas, SRDJC-15 excelled in terms of individual fruit weight, pulp content, and seed weight. Among the genotypes, SRDJC-04 recorded the highest Total Soluble Solids (TSS) value (20.76 °Brix), followed by SRDJC-16 (20.23°Brix), while the lowest was found in SRDJC-15 (10.13°Brix). The sweetness, measured as the TSS-to-acid ratio values was observed in SRDJC-16 (15.13), followed by ADBJC-01 (13.29) and SRDJC-04 (12.43). Despite the low yield of SRDJC-04 (14.35 kg tree-1), it has been identified as a promising genotype for table purpose with high pulp content and total soluble solids. The superior performance of SRDJC-03 and other genotypes over the national check Konkan Bahadoli further require multi-location field trials to validate the performance.